Financial Performance As A Determinant Of Firm Value: The Moderating Influence Of Good Corporate Governance In Indonesian LQ45 Companies - Weni Susanti; Amita Tarina Maieva; Eri Triharyati; Yuli Nurhayati; Indrawati Mara Kesuma (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of financial performance on firm value, with Good Corporate Governance (GCG) as a moderating variable. This research is quantitative in nature. The population in this study consists of companies listed in the LQ45 Index of the Indonesia Stock Exchange (IDX), totaling 45 companies. The sample selection was conducted using the purposive sampling method, resulting in 19 companies that met the sampling criteria. The research method used is panel data regression analysis, with data processing performed using Eviews 12. The data collection technique employed in this study is document analysis, which involves gathering data from literature reviews and the annual reports of LQ45 companies for the 2020-2023 period. The data source used in this research is secondary data. The results indicate that ROA and ROE have a significant effect on firm value, as measured by Tobin's Q. Additionally, GCG, measured by institutional ownership, is proven to moderate the relationship between ROA and firm value but does not moderate the relationship between ROE and firm value. These findings highlight the importance of implementing GCG in enhancing firm value, particularly in the context of the Indonesian capital market. This research is expected to contribute to academic literature, and future researchers are encouraged to expand their insights for reference in subsequent studies.